QuantifyingtheImpactofUncertainMaterialParametersonPavement ResponseusinganInverseModellingTechnique - Kathirgamanathan, P.; Vignarajah, M. (KDU International Research Conference, 2023)
Accuratemodellingofpavementresponseplaysacriticalroleintheeffectivedesign, analysis,andmaintenanceofroadinfrastructure.However,thepresenceofuncertainty inmaterialparameterscansignificantlycompromisethereliabilityandaccuracyofsuch models.Thisstudyfocusesoninvestigatingtheimpactofuncertainmaterialparameters onpavementresponsebyemployinganinversemodellingtechnique.Theobjectiveofthis researchistoutilizeaninversemodellingapproachtoassesstheinfluenceofuncertain materialparametersonUzan’smodel,acommonlyusedmodelforpavementresponse. ThestudyconsidersmeasuredstressandstrainvaluesobtainedfromtyreandFalling WeightDeflectometerloadconditionsappliedtogranularmaterials.Theinversemodel isformulatedasanonlinearleastsquaresminimizationproblem,inconjunctionwith afiniteelementmodelthatanalysesthedeformationofflexiblepavements.Through theapplicationoftheinversemodellingtechnique,thisstudyaimstodeterminethe extenttowhichuncertainmaterialparametersaffecttheaccuracyofpavementresponse predictions.Bycomparingthepredictedpavementbehaviourderivedfromtheinverse modelwithactualmeasureddata,theinfluenceofuncertainparameterscanbequantified. Theoutcomesofthisresearchcontributetoadvancingtheunderstandingofthecomplex interplaybetweenmaterialparameteruncertaintiesandpavementresponse.
Keywords: Finite element modelling; Inverseproblem; Parameterestimation; Pavement response